PENGARUH PEMBELAJARAN KEWIRAUSAHAAN, SIKAP KEWIRAUSAHAAN, DAN MOTIVASI KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA (STUDI PADA ANGGOTA KOMUNITAS SOSIAL-ENTREPRENEUR LAKOAT KUJAWAS) - Maria Prilia Karibera; Rolland E Fanggidae; Ni Putu Nursiani; Alexandre Desousa Guterres (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of Entrepreneurial Learning, Entrepreneurial Attitudes, and Entrepreneurial Motivation on the Entrepreneurial Intention of the Lakoat Kujawas community. This is a quantitative research. The population in this study were all members of the Lakoat Kujawas community. The sampling technique in this study was saturated sampling, with a total of 35 respondents. The analysis technique in this study is Multiple Linear Regression preceded by the classical assumption test with the assistance of SPSS V.21. Hypothesis testing is done by t-test test. The results of the partial hypothesis test show that Entrepreneurial Learning has a positive and significant on the Entrepreneurial Intention, Entrepreneurial Attitude has a positive and but not significant effect on the Entrepreneurial Intention, and Entrepreneurial Motivation has a positive and significant on the Entrepreneurial Intention of the Lakoat Kujawas community. Keywords: Entrepreneurial Learning; Entrepreneurial Attitudes; Entrepreneurial Motivation; Entrepreneurial Intention